Bit-Interleaved Space-Time Coded Modulation with iterative decoding - Shahid, Iqbal; Rajatheva, R.M.A.P; Poompat Saengudomlert; Erke, Tapio J.; Higher Education Commission (HEC), Pakistan; Asian Institute of Technology Fellowship (Pathum Thani, Thailand : Asian Institute of Technology, 2007)
Bit Interleaved Code Modulation (BICM) was first introduced by Zehavi (Zehavi, 1992) to improve the performance of a coded modulation scheme over fading channels. Biglieri (Biglieri et.al, 1998) then formally introduced the idea alongwith the complete and detailed performance analysis. In order to cope with the shortcomings of BICM over AWGN channels as compared to conventional Trellis Coded Modulation (TCM) schemes, Li (Li et al., 1997) introduced iterative decoding on the receiver side. Space-Time BICM is supposed to improve the performance of conventional Space-Time systems in both AWGN and fading scenarios. In this thesis, we first discuss the performance of Space-Time BICM over correlated fading channels which is an untouched area until now. We consider both Rayleigh and Rician fading channels and assume symmetrical correlation model. Numerical results are also shown to supplement the theoretical derivations. As another application of BICM, we discuss BICM with Adaptive Modulation and Coding (AMC) in the physical layer alongwith the effects of queuing in the data link layer. This is a kind of cross-layer analysis where we optimize the packet dropping rate due to queuing and packet loss rate due to non-ideal channel conditions. Numerical results show that the performance of the given systems increase considerably when BICM is applied as compared to the case without any bit-wise interleaving
A thesis submitted in partial fulfillment of the requirements for the degree of Master of Engineering in Telecommunications
Thesis (M.Eng.) - Asian Institute of Technology, 2007
Keywords: Space time codes; Interactive methods (Mathematics); Error-correcting codes (Information theory)